Literature Review: Ekosistem Lamun sebagai Bioindikator Pencemaran Lingkungan Pesisir - Wasniatun, Wasniatun (Biocaster : Jurnal Kajian Biologi, 2024)
Seagrass ecosystems are among the ecosystems found in coastal areas. Seagrass beds consist of one or more seagrass species interacting with biotic and abiotic factors in their environment. The objective of this study is to describe the potential of seagrass ecosystems as bioindicators of coastal environmental pollution. The method used in writing this article is a literature review. Articles were collected through literature searches using selected sources (databases) such as Google Scholar. The search covered journal articles published from 2013 to 2023. The research results show that seagrass species are highly diverse along coastal waters. Several seagrass species have been detailed in the study findings. Furthermore, seagrasses have potential as bioindicators of environmental pollution, particularly in assessing the water quality of coastal areas. For instance, seagrasses serve as bioaccumulators of heavy metals such as Cu, Cd, Pb, and Zn in aquatic environments.